2011
DOI: 10.1093/heapro/dar034
|View full text |Cite
|
Sign up to set email alerts
|

A nutrition labeling intervention in worksite cafeterias: an implementation evaluation across two large catering companies in the Netherlands

Abstract: SUMMARYBy both increasing the availability of healthy foods and labeling these products with the Choices logo, caterers may facilitate employees to make a healthier choice in their worksite cafeterias. The aim of this study was to explore which attributes influence the implementation of the Choices logo in worksite cafeterias in the Netherlands. Questionnaires were completed by catering managers of 316 cafeterias of two large caterers in the Netherlands (response rate 49.8%). Attributes from the Diffusion of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Furthermore, the results suggested that the intervention was promising in terms of feasibility and continued use, especially because research has indicated that compatibility and complexity in the sense of time were predictors for the degree of implementation of the ‘Choices logo’ (i.e. a front‐of‐pack logo on products that are a healthy choice within a food category) in Dutch worksite cafeterias (Vyth et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results suggested that the intervention was promising in terms of feasibility and continued use, especially because research has indicated that compatibility and complexity in the sense of time were predictors for the degree of implementation of the ‘Choices logo’ (i.e. a front‐of‐pack logo on products that are a healthy choice within a food category) in Dutch worksite cafeterias (Vyth et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies used mostly quantitative data collection methods (n = 8), followed by qualitative (n = 7) and mixed methods (n = 2). Only two studies used an explicit theory and in both instances, the Diffusion of Innovation Theory [56,57]. The study setting ranged from small independently owned restaurants to large foodservice corporations including chain and franchise restaurants, as well as large catering companies.…”
Section: Study Characteristics and Quality Appraisalmentioning
confidence: 99%
“…Several studies have found that health concern is a primary motivational factor for buying organic food (Lockie et al 2002;Magnusson et al 2003;Ureña et al, 2007;de Magistris and Gracia, 2008;Pohjanheimo et al, 2010;Januszewska et al, 2011;Vyth et al, 2012;Dowd and Burke, 2013;Russell et al, 2015;Hilverda et al, 2016;Bryla, 2016). ; Asif et al, 2018;Goetzke et al, 2014;Eisinger-Watzl et al, 2015;Hansen et al, 2018).…”
Section: Literature Review and Research Hypotheses Organic Food Consumption Motivationsmentioning
confidence: 99%